The Constitutional Courts in the face of the Health Emergency due to COVID-19 - Cadena Alcalá, Jesús Ángel (2020)
The purpose of this text is to analyse the privileged position of the constitutional courts in regards to the full custody and stability of constitutional texts. Recent world scenarios have shown the need for such courts to respond to social demands, especially when the actions of public authorities tend to undermine the proper and effective exercise of the rights, freedoms and principles recognized in constitutional texts and international human rights law. For them, the interpretation and constitutional argumentation is a bastionwith which they can analyze the validity of the acts of the public powers that limit or restrict fundamental rights, seeking to contain their actions when they are contrary to the values on which it is based the constitutional State of Law.